Safety evaluation of the Guardian device on the common carotid artery in sheep. Issue 4 (April 2023) - James, Natalie L.; Milijasevic, Zoran; Ujhazy, Anthony; Huber, David; Rotne, Randi; Edwards, Glenn; Jermyn, Kieri; Celermajer, David S.
Abstract: Background: Pulse pressure intensity in middle-aged adults is a risk factor for dementia. The Guardian device (The Brain Protection Company, Sydney, Australia) has been developed to reduce pulse pressure, as a potential therapy. Objectives: The aim of this study was to evaluate the safety of the Guardian, a novel pulse modulation device designed to reduce the intensity of the pulse pressure that penetrates into the cerebral small vessels. The Guardian is a helix that gently wraps around the common carotid artery (CCA) to slightly change its shape, to absorb pulsatility, without lowering flow. Methods: The Guardian was implanted bilaterally on the CCAs of 10 mature sheep for chronic implant periods of 3, 6 or 8 months. The ratio of internal device diameter to outer diameter of the CCA varied from 63% to 92% (n = 20). The implant position on the vessel was marked surgically at implant. Gross pathology and histopathology of the CCA were examined at 3- and 6-months post explant. Most devices were explanted using open surgery, however minimally invasive surgical explant techniques were examined in 2 animals to assess the potential of this approach for explant in humans if required. Results: The Guardian was successfully implanted with no adverse events, and minimally invasive explant appeared to be viable for removal. Following implant, the device was surrounded by a thin fibrous capsule, with similar pathology at 3- and 6-months. Minimal or no movement was observed. CCA sections appeared histologically normal, with no evidence of thrombosis, stenosis, fibrosis, chronic inflammatory response, or vessel degeneration. Conclusions: The feasibility of surgical implantation and biomaterial safety of the Guardian was confirmed over 8 months. Minimally invasive explant of the Guardian has the potential to be viable. Further work is required to demonstrate efficacy in vitro and/or in vivo before evaluation in humans. Highlights: Guardian device biomaterial safety was demonstrated in a sheep model. Guardian devices were implanted bilaterally on common carotid arteries for up to 8 months. Potential for surgical explant via minimally invasive surgery if required.